1998
DOI: 10.1584/jpestics.23.29
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cold Resistance in Rice Seedlings by 5-Aminolevulinic Acid

Abstract: 5-Aminolevulinic acid (ALA) at low concentrations increased cold resistance in rice seedlings. The pretreatment of rice seedlings by root-soaking with ALA solution at 0.1-1 ppm reduced the ratio of leaf rolling and electrolyte leakage from leaf tissue after cold treatment. Thirty days after cold treatment at 5C for 5 days, the plants treated with 1 ppm ALA resulted in 85% survival ratio, 6.1 leaves per plant and 111.8 mg dry weight per aerial part of seedling, while 65%, 5.9 and 65.0 mg respectively in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 9 publications
(9 reference statements)
0
45
0
Order By: Relevance
“…Exogenous low concentrations of ALA have been reported to alleviate the harmful effects caused by water-deficit stress to some degree, by increasing chlorophyll biosynthesis, photosynthesis, and cold and salt tolerance (Hotta et al, 1997;Hotta et al, 1998;Watanabe et al, 2000a). Recently, Zhen and colleagues found that ALA application can counteract the oxidant damage induced by salt in cucumber leaves and upregulated the expression of catalase and cytosolic ascorbate peroxidase genes in the leaves (Zhen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous low concentrations of ALA have been reported to alleviate the harmful effects caused by water-deficit stress to some degree, by increasing chlorophyll biosynthesis, photosynthesis, and cold and salt tolerance (Hotta et al, 1997;Hotta et al, 1998;Watanabe et al, 2000a). Recently, Zhen and colleagues found that ALA application can counteract the oxidant damage induced by salt in cucumber leaves and upregulated the expression of catalase and cytosolic ascorbate peroxidase genes in the leaves (Zhen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…14) Moreover, the amelioration of some environmental stresses by ALA has also been reported. [15][16][17] The resistance to cold stress in rice seedlings 15) and salt tolerance in cotton 16) and spinach 17) increased after ALA treatment. Seed germination of pakchoi (Brassica camprestris ssp.…”
Section: Introductionmentioning
confidence: 99%
“…ALA is a biodegradable herbicide and insecticide, but it has promotional effects on the growth and photosynthesis of crops and vegetables, and is harmless to humans, animals, and crops (Sasaki et al, 1993;Hotta et al, 1997aHotta et al, 1997b. The compound presumably promoted the chilling tolerance effect in plants under low-light which suppressed respiration (Hotta et al, 1998;Wang et al, 2004), and improved tolerance to salinity stresses (Nishihara et al, 2003). ALA not only promotes the growth and yield of crop plants, but also acts as an alleviator of oxidative damage and enhances the activity of antioxidant enzymes such as superoxide dismutase (SOD), peroxidase (POD), and ascorbate peroxidase (APX) to encounter radicals under stress conditions i.e., drought stress and NaCl stress (Nishihara et al, 2003;Li et al, 2011;Liu et al, 2011).…”
mentioning
confidence: 99%